Brain-immune interactions in health and disease - Adam Denes (Frontiers Research Topics, 2015)
Brain-immune interactions are essential to maintain health and their dysfunction contributes to diverse human diseases. Recent data show that haematopoietic processes and immune organs are under central autonomic control. Deficient regulation of inflammatory events contributes to brain diseases, whereas acute or chronic brain injury is linked with the development of systemic inflammatory conditions or immunosuppression. At present, common disorders with high socio-economic burden such as cancer, cardiovascular-, neuroinflammatory- and neurodegenerative diseases, asthma, allergies, autism, psychiatric conditions and sepsis are believed to be influenced, at least in part, by the dysfunction of brain-immune communication. Since the median age of the world's population is increasing rapidly, it is expected that the burden of common non-communicable diseases will further increase, which represents a huge challenge to the health care systems worldwide. Thus, there is an increasing demand to understand and treat complex diseases, many of which are age-related, and this is not possible unless the fine-tuned communication between large systems -such as the nervous and the immune system- is comprehensively understood. Although it is impossible to cover all areas of relevant research in this field, papers in this eBook give some insight to a few important aspects of brain-immune interactions and their contribution to disease. We hope that this collection could stimulate further relevant research and facilitate discussions to support the understanding of the highly complex interactions between the immune system and the brain in health and disease.